Integrating Sandur Madura as a Cultural Context in Science Education: An Ethnographic Study on Migration and Acculturation in West Kalimantan - Mega Cantik Putri Aditya; Aline Rizky Oktaviari Satrianingsih; Regaria Tindarika (Jurnal Penelitian Pendidikan IPA, 2025)
Immigration by Madurese natives in West Java was carried out due to economic and geographical factors and supported by an independent, dynamic, and courageous nature. This economic factor is indicated by the still high poverty rate in East Java and the high level of competition in getting jobs. Migration is an option for Madurese people to find sources of life that are starting to be limited; one of the migration destinations is in West Kalimantan. Many Madurese people migrate to West Kalimantan because they already have relatives there and have opportunities to improve their economy. This migration certainly affects the culture of the community, where Madura has a culture that must be maintained by its people even though they are outside the Madura area; the goal is to preserve and maintain the culture. Sandur is one of the Madurese cultures in the form of a theatre performance that integrates music, dance, and acrobatic silat movements. Education is one of the keys to preserving Madurese culture for immigrant communities in West Kalimantan. The method used is a qualitative ethnographic approach through observation and structured in-depth interviews to understand the dynamics and interactions of the Madurese ethnic group with local ethnic groups. The results of the study show that the Sandur performing arts not only function as entertainment, but also as a means of social education that conveys moral and ethical values, a bridge of acculturation. The process of enculturation and acculturation creates cultural harmony that enriches the identities of both parties, marked by the modernization of Sandur in its performances to adapt to local culture in West Kalimantan. The existence of a curriculum that supports Sandur culture can support students' sense of pride and active participation so that students will have awareness and participate in preserving Sandur culture. These findings support the integration of local cultural values into science education, fostering both scientific literacy and cultural identity among students.